RIG-I specifically mediates group II type I IFN activation in nervous necrosis virus infected zebrafish cells. Issue 2 (April 2015) - Chen, Hsu-Yu; Liu, Wangta; Wu, Sung-Yu; Chiou, Pinwen Peter; Li, Yen-Hsing; Chen, Yen-Chun; Lin, Gen-Hwa; Lu, Ming-Wei; Wu, Jen-Leih
Abstract The type I interferon (IFN) response has been shown to be crucial for the survival of zebrafish larvae infected with nervous necrosis virus (NNV). Teleost type I IFNs can be divided into two groups, based on their cysteine content. While teleost group I IFNs have been extensively studied in terms of their regulation and anti-viral properties, the characteristics of teleost group II IFNs have been relatively unexplored. In this study, we describe the mechanism by which group II IFNs are activated in response to NNV infection in a zebrafish cell line, by focusing on the relationship between type I IFNs and pattern recognition receptors. Expression profile analysis of infected cells by microarray and qPCR revealed signaling activation of two pattern recognition receptors (PRRs): RIG-I like receptors (RLRs) and MyD88-dependent Toll-like receptors (TLRs). Knockdown of retinoic acid-inducible gene I (RIG-I) specifically repressed induction of group II IFNs (IFNϕ2, IFNϕ3) by NNV infection. Furthermore, Ingenuity Pathway Analysis (IPA) was used to demonstrate that RIG-I knockdown results in down-regulation of the inflammatory response in NNV-infected cells. Taken together, our results indicate that RIG-I plays an essential role in zebrafish group II type I IFN induction and the inflammatory response to NNV infection.